Traditional neighborhood adaptive reuse in the old city Sana'a, Yemen / Laila Ahmed Haidar and Anuar Talib - Ahmed Haidar, Laila; Talib, Anuar (Universiti Teknologi MARA Cawangan Selangor, 2018)
The study aims to identify the current conditions of the traditional neighbourhood (Hara) environment of Sana’a old city and to evaluate the outcomes of adaptive reuse. A case study of Hara Al-Abhar was made with the following instruments: On-site spatial observation and measurements and in-depth structured interviews. The study revealed the enhancement of income to house owners and the revival of traditional handicrafts. The disadvantage is that it disturbs the resident's privacy with the increment of vehicular accessibility and previously open public spaces and streets becoming parking spaces. This led the womenfolk to retreat into their houses.